KAJIAN YURIDIS PENERAPAN SANKSI PIDANA DALAM KASUS TINDAK PIDANA PERSETUBUHAN YANG DILAKUKAN OLEH ANAK TERHADAP ANAK (Studi Kasus Putusan Pengadilan Negeri Pemalang Nomor: 3/Pid.Sus-Anak/2018/PN Pml) - KURNIAWAN, TEDY VERDYANTO (Dinamika Hukum, 2019)
The purpose of this research is to examine the application of criminal sanctions in case of a criminal offence committed by a child to a child in the decision of the District Court of Pemalang number: 3/Pid. Sus-Child/2018/PN Pml. The method of approach in writing is normative juridical. The specification of this research uses analytical descriptive. The data source uses the Skunder data. Data collection techniques using library studies. To analyze the data, researchers use qualitative descriptive analysis methods. Based on the results of the study obtained the conclusion that the application of criminal sanctions in the case of a criminal offence committed by a child to a child in the decision of the District Court of Pemalang number: 3/Pid. Sus-Child/2018/PN PML based on Law No. 11 year 2012 on the Children's criminal justice system is carried out by the judge to give the verdict in the form of imprisonment for 10 (ten) months and must participate in the employment training at the Training Institute for 3 (three) months according to the authors is appropriate because the defendant's child has tried 14 years and the demand for his criminal above 7 (seven) years so that it is not mandatory to be made in the version. Judgment of judges on the defendant's child in the case of a criminal offence is based on a tool proof of witness information, information of experts, letters, instructions and information of the defendant and refers to article 81 paragraph (2) of LAW No. 23 year 2002 on Child protection Jo UU No. 11 Year 2012 on child criminal justice system as well as the description of parents of children are related to the report on the results of societal research. Key words: criminal offence, child criminal justice system.